Can oil prices forecast exchange rates? An empirical analysis of the relationship between commodity prices and exchange rates. (June 2015) - Ferraro, Domenico; Rogoff, Kenneth; Rossi, Barbara
Abstract: We show the existence of a very short-term relationship at the daily frequency between changes in the price of a country's major commodity export and changes in its nominal exchange rate. The relationship appears to be robust and to hold when we use contemporaneous (realized) commodity price changes in our regression. However, when we use lagged commodity price changes, the predictive ability is ephemeral, mostly appearing after instabilities have been appropriately taken into account. Highlights: We study whether commodity prices have a reliable and stable out-of-sample relationship with the Canadian/U.S. exchange rate. We show the existence of a short-term relationship at the daily frequency, especially when using contemporaneous (realized) oil prices. When using lagged oil prices as predictor, the predictive ability is ephemeral, appearing only after taking into account instabilities. In contrast, unsurprisingly, we find little systematic relation between oil prices and exchange rates at monthly/quarterly frequencies.